You can do it, Bert! - Könnecke, Ole, 1961- (Gecko Press, 2014)
Burt was mentally and physically prepared. He checked everything. Again and again. He hesitated. There was something missing-- Oh yes! Refreshment. Not that Burt tried to retreat, no, no, he has just gone for a banana. Maybe if his friends had not all encouraged him, Burt would not dare. But they shouted BURT! because they believed. And it is then, and only then, that Burt felt ready. And he did it.